Radicals in synthesis III - Gansauer, Andreas; Heinrich, Markus (Topics in Current Chemistry, 2012)
Siegfried R. Waldvogel Stamo Mentizi Axel Kirste Boron-Doped Diamond Electrodes for Electroorganic Chemistry Gerald Pratsch Markus R. Heinrich Modern Developments in Aryl Radical Chemistry Gregory K. Friestad Radical Additions to Chiral Hydrazones: Stereoselectivity and Functional Group Compatibility Andreas Gansäuer Lei Shi Matthias Otte Inga Huth Antonio Rosales Iris Sancho-Sanz Natalia M. Padial J. Enrique Oltra Hydrogen Atom Donors: Recent Developments Ullrich Jahn Radicals in Transition Metal Catalyzed Reactions? Transition Metal Catalyzed Radical Reactions? - A Fruitful Interplay Anyway Part 1. Radical Catalysis by Group 4 to Group 7 Elements Ullrich Jahn Radicals in Transition Metal Catalyzed Reactions? Transition Metal Catalyzed Radical Reactions? - A Fruitful Interplay Anyway Part 2. Radical Catalysis by Group 8 and 9 Elements Ullrich Jahn Radicals in Transition Metal Catalyzed Reactions? Transition Metal Catalyzed Radical Reactions?: A Fruitful Interplay Anyway Part 3: Catalysis by Group 10 and 11 Elements and Bimetallic Catalysis